Art as material sublimation: Tarkovsky's zone and Bukowski's firefly- poems (Mayéutica Revista Científica de Humanidades y Artes, 2026)
This paper analyzes the conception of art as material sublimation based on the works of filmmaker Andrei Tarkovsky and writer Charles Bukowski. From a materialist perspective, reality is understood as a dynamic field of forces. Within this framework, sublimation does not imply a transcendence toward the immaterial, but rather an effective encounter between the work of art and the viewer in which the latter finds a connection with the virtual dimension of the artistic material. Two central figures are examined: the “zone” from the film Stalker and Bukowski’s “firefly poems.” In the first case, the zone appears as a space of connection with the infinite, activated by desire. In the second, everyday and marginal experience is transformed into poetic flashes. Finally, the relationship between sacrifice and salvation is addressed, highlighting the vital, communal, and open dimension of art.
Keywords: Nietzsche; Tarkovsky; Bukowski; materialism; art